Magnetically modified MgO nanoparticles as an efficient adsorbent for phosphate ions removal from wastewater. Issue 11 (23rd July 2020) - Habiby, Seyyed Rasoul; Esmaeili, Hossein; Foroutan, Rauf
ABSTRACT: In this research, MgO/Fe3 O4 nano-composite was synthesized and characterized by different analyses including SEM, MAP, EDX, XRD, VSM, FTIR, and BET. The results showed that the adsorbent was super paramagnetic with a specific surface area of 75.2 m 2 /g. Also, the adsorption study showed that the maximum adsorption efficiency of phosphate (98.9%) was obtained at pH value of 9, temperature of 25°C, contact time of 20 min, the adsorbent dosage of 5 g/L, and phosphate ion concentration of 1 mg/l. Additionally, the experimental data were adequately fitted with the pseudo-second-order kinetic model. Moreover, thermodynamic parameters revealed that the adsorption process was spontaneous and exothermic . Generally, the results revealed a good efficiency of MgO/Fe3 O4 nano-composite in removing phosphate ions.